Penegakan Hukum terhadap Korporasi sebagai Pelaku Tindak Pidana Pencemaran Air - Fatur Faturohman (Savana, 2024)
The increase in economic needs in a society causes one of the basic human rights to be violated by corruption perpetrators, the existence of waste pollution carried out by PT. Sari Inti Prima Perkasa due to leakage of wastewater treatment installations causes the river and land of residents around the location of PT. Sari Inti Prima Perkasa to experience a decline in environmental quality. The purpose of this study is to determine the role of criminal law in enforcing the law, and efforts that can be made to realize environmental sustainability and preservation. This research method is normative legal research by delving deeper into secondary information in the form of literature reviews and related laws and regulations. Primary legal materials are laws and regulations such as Law Number 32 of 2009 concerning Environmental Management and Protection, Government Regulation Number 101 of 2014 concerning Management of Hazardous and Toxic Waste, and Government Regulation Number 22 of 2021 concerning Implementation of Environmental Protection and Management and Decision Number: 168 / Pid.BLH / 2023 / PN.Bls. The results of the study are based on Decision Number: 168/Pid.BLH/2023/PN.Bls, which sentenced the Defendant to 1 (one) year in prison and a fine of Rp. 100,000,000 (one hundred million rupiah) with the provision that if the fine is not paid, it will be replaced with imprisonment for 1 (one) month. The conclusion is that environmental criminal law enforcement has been carried out in accordance with the laws and regulations in force in Indonesia. The suggestion is to encourage collaboration and coordination between every stakeholder in the community in order to protect the environment and more massive law enforcement in realizing environmental sustainability and sustainability.